Dental lasers applications in visible wavelength operational band - Mahmoud M. A. Eid; Iraj Sadegh Amiri; Ahmed Nabih Zaki Rashed; Preecha Yupapin (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
There is no doubt that radiation has many side effects in our lives, so our goal in this study is to reduce our use of radiation in the diagnosis of tooth caries, and in order to achieve this goal we used the field of optical fiber in the detection of some diseases associated with oral and dental medicine. This diagnosis was accomplished by shedding light on the teeth, to be diagnosed and creating an image that allows the doctor to examine them and determine whether there are caries or any root problems. The principle is also used to detect oral cancer, fractures, and cracks in bones. This study also allows us to detect early caries, and this method saves time because it gives the diagnosis at the same time while the patient is in the treatment unit of the dental clinic. Thus the main advantages of this method are, enable the dentist to view images on the display unit attached to the clinic in real-time, compare current photos with old photos of the same patient. Also, the dentist can create a photo archive of each tooth individually and can retrieve and compare them whenever he wants.